Access to P‐ and Axially Chiral Biaryl Phosphine Oxides by Enantioselective CpxIrIII‐Catalyzed C−H Arylations. Issue 39 (29th August 2018) - Jang, Yun‐Suk; Woźniak, Łukasz; Pedroni, Julia; Cramer, Nicolai
Abstract: An enantioselective C−H arylation of phosphine oxides with o ‐quinone diazides catalyzed by an iridium(III) complex bearing an atropchiral cyclopentadienyl (Cp x ) ligand and phthaloyl tert ‐leucine as co‐catalyst is reported. The method allows access to a)  P ‐chiral biaryl phosphine oxides, b) atropo‐enantioselective construction of sterically demanding biaryl backbones, and also c) selective assembly of axial and P ‐chiral compounds in excellent yields and diastereo‐ and enantioselectivities. Enantiospecific reductions provide monodentate chiral phosphorus(III) compounds having structures and biaryl backbones with proven importance as ligands in asymmetric catalysis. Abstract : An enantioselective C−H arylation of phosphine oxides with o ‐quinone diazides is catalyzed by a Cp x Ir III complex and chiral carboxylic acid co‐catalyst. It provides a unifying access to P ‐chiral phosphine oxides, atropo‐enantioselective construction of sterically demanding biaryl backbones, and a selective assembly of axial and P ‐chiral compounds in excellent yields and diastereo‐ and enantioselectivities.